ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES SYNTHESIZED USING ELEUSINE INDICA (L.) GAERTN. LEAF EXTRACT ON THE BACTERIA ISOLATED FROM THE VASE SOLUTION - Thi Anh Tu Le (Tạp chí Khoa học Đại học Đà Lạt)
Green synthesis of silver nanoparticles (SNPs) using Eleusine indica (L.) Gaertn. leaf extract as a reducing agent is reported. SNPs were characterized with UV-Vis spectroscopy and transmission electron microscopy (TEM). The SNPs were rod like and spherical in shape with sizes from 3 to 33 nm and an average size of 16.73 nm. Seven bacterial strains were isolated from the vase water, including Bacillus cereus CA1, Alcaligenes faecalis CA2, Micrococcus luteus CA3, Pantoe agglomerans CA4, Pseudomonas aeruginosa CA5, Pseudomonas aeruginosa CA6, and Pantoe agglomerans CA7. Identifications were made according to Bergey’s Manual of Systematic Bacteriology and Bergey’s Manual of Determinative Bacteriology. The SNPs inhibited the growth of bacteria and exhibited significant antimicrobial activity against different isolated bacteria strains. SEM images showed that the SNPs damaged the cell membranes of bacteria, released plasmic contents, and altered the morphology of the cells. The impact of SNPs on gram-negative bacteria was more severe than on gram-positive bacteria. This study revealed that biosynthesized SNPs from Eleusine indica (L.) Gaertn. leaf extract are potential agents in combating bacterial contamination.